2018
DOI: 10.20945/2359-3997000000038
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of sentinel lymph node mapping in detecting occult neck metastasis in papillary thyroid carcinoma

Abstract: For this series of cN0 PTC patients: 1) SLNM accuracy was 97%, and 2) SLNM upstaging from cN0 to pN+ was 49%, whereas to stages III and IVa, it was 21%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In different reports, PTC is shown to involve cervical lymph node metastasis in 20-50% of patients with macrometastasis and in up to 90% of patients with micrometastasis detected by sensitive detection methods (9)(10)(11). LNM of PTC occurs in a stepwise fashion.…”
Section: Introductionmentioning
confidence: 96%
“…In different reports, PTC is shown to involve cervical lymph node metastasis in 20-50% of patients with macrometastasis and in up to 90% of patients with micrometastasis detected by sensitive detection methods (9)(10)(11). LNM of PTC occurs in a stepwise fashion.…”
Section: Introductionmentioning
confidence: 96%
“…By definition [ 32 ], skip lesions were revealed as positive SLNM in 14% in the current analysis. Studies have reported an accuracy of SLNM in detecting LN in the central compartment in up to 97%, though only up to 33% in the lateral compartment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reported occult metastasis rate of PTC was about 27% to 90% ( 29 , 33 35 ). In our study, we reviewed the preoperative ultrasonographic reports of all patients who underwent BCLND, and found that the rate of occult lymph node metastasis is 25.42%.…”
Section: Discussionmentioning
confidence: 99%